The association between pre-operative pain experience and post-operative pain in patients undergoing elective gastrointestinal surgery: a descriptive-comparative study - Hertsman, Yehonatan (My University, 2023)
Aims: The purpose of the rapid review was to summarize and aggregate information for researchers and clinicians about predisposing factors for post-operative pain in laparoscopic patients and the prevalent management approaches post-operatively. The purpose of the descriptive-comparative study was to explore the associations between previous pain experiences and medication on the intensity of pain post-operatively in patients undergoing elective gastrointestinal surgery, using data collected by the Smart Pain Assessment Tool Based on Internet of Things. Methods: For the rapid review, the databases of PubMed, Web of Science and Embase were searched. ROBINS-I tool was used to evaluate the quality of non-randomized studies while ROB 2 tool was used for randomized controlled trials. For the descriptive-comparative study, 50 patients after gastrointestinal operations at Turku University hospital were included. The data collection of the study was done by a researcher belonging to Turku University staff at Turku University hospital. The data analysis was done by using descriptive and comparative methods of analysis. Descriptive statistics were used for the presentation and analysis of participants outcomes, diagnoses, procedures, and groupings based on variables related to the experience of pain (e.g., graphical measurement maximal pain levels using the numeric rating scale). Comparative statistics were used for associations and correlations regarding previous pain levels, medications, fear, and expectation of pain on maximal pain levels after gastrointestinal operations at Turku University Hospital. Results: The result of the rapid review suggest many predisposing factors for post-operative pain are influenced by the psychological profile of the patient. Among these factors are anxiety, fear, depression, expectation of pain, and other factors related to gastrointestinal surgery. Nevertheless, the results of this review also describe acute pre-operative pain, surgical factors, genetics, age, gender, obesity, and previous experiences of pain as relevant predisposing factors to pain following gastrointestinal surgery. Pain care strategies following gastrointestinal surgery include the use of pharmacological and non-pharmacological interventions. The literature suggests, non-pharmacological interventions are under-utilized and should be encouraged as an adjunct to pharmacological pain control strategies following elective gastrointestinal surgery. The results of the descriptive-comparative study somewhat contradict the results of the rapid review. Previous pain experiences or the recollection of preceding painful events were not associated with the administration of supplemental pain medication post-operatively (p = 0.741). Fear related to the upcoming pain following surgery was not associated with the level of invasiveness of the surgery (p = 0.662). In addition, the relationship between expectation of pain (p = 0.698), fear of pain related to the upcoming surgical procedure (p = 0.637) and medication post-operatively (p = .481) on the intensity of maximal post-operative pain was found to be negligible. The results of this study suggest patient expectation as a possible domain of intervention for better pain outcomes post-operatively. The administration of pain medication in the recovery room and the amount of pain medication in the recovery room were significant predictors of maximal post-operative pain (p = .001). Discussion: The results of the rapid review suggest a high to critical risk of bias in the studies included. The predisposing factors for post-operative pain differed widely across studies, but mainly included psychological factors as factors for post-operative pain. Pain management strategies should include an individualized approach and be implemented before, during and after the operation. For the descriptive-comparative study, there are substantial difficulties in discerning the effect of pain history or experience on post-operative pain using physiological or subjective reporting for conscious individuals due to risk of bias and using a unidimensional approach. Conclusion: Predisposing factors for post-operative pain should be screened in the pre-operative phase if possible, focusing on addressable factors whereas management of pain care strategies should include careful screening of participants biopsychosocial profile for elective surgery. The descriptive-comparative study suggests a possible, yet minimal benefit for managing patients’ expectation of pain related to the upcoming gastrointestinal surgery. The amount of pain medication in the recovery room is a significant predictor of maximal post-operative pain. Future research should include a larger sample, more variables related to pain and continue with a follow-up. Keywords: gastrointestinal, post-operative, pain, analgesia, anesthesia

Tavoitteet: Katsauksen tarkoituksena oli tiivistää ja koota yhteen tutkijoille ja kliinikoille tietoa laparoskooppisten potilaiden postoperatiiviselle kivulle altistavista tekijöistä ja vallitsevista postoperatiivisista hoitokeinoista. Kuvailevan-vertailevan tutkimuksen tarkoituksena oli tutkia aiempien kipukokemusten ja lääkityksen välisiä yhteyksiä postoperatiivisen kivun voimakkuuteen potilailla, joille tehdään elektiivinen ruoansulatuskanavan leikkaus, käyttäen tietoja, jotka on kerätty esineiden internetiin perustuvalla älykkäällä kivunarviointityökalulla. Menetelmät: Katsausta varten tehtiin hakuja PubMed-, Web of Science- ja Embase-tietokannoista. ROBINS-I-työkalua käytettiin satunnaistamattomien tutkimusten laadun arviointiin, kun taas satunnaistettujen kontrolloitujen tutkimusten osalta käytettiin ROB 2-työkalua. Kuvailevaan-vertailevaan tutkimukseen otettiin mukaan 50 potilasta Turun yliopistollisessa sairaalassa tehtyjen ruoansulatuskanavan leikkausten jälkeen. Tutkimuksen aineistonkeruun suoritti Turun yliopiston henkilökuntaan kuuluva tutkija Turun yliopistollisessa sairaalassa. Aineiston analysoinnissa käytettiin kuvailevia ja vertailevia analyysimenetelmiä. Kuvailevia tilastoja käytettiin osallistujien tulosten, diagnoosien, toimenpiteiden ja kivun kokemiseen liittyvien muuttujien perusteella tehtyjen ryhmittelyjen esittämiseen ja analysointiin (esim. maksimaalisen kiputason graafinen mittaaminen numeerisella arviointiasteikolla). Vertailevia tilastoja käytettiin yhdistelmiin ja korrelaatioihin, jotka koskivat aiempia kiputiloja, lääkkeitä, pelkoa ja kivun odotusta maksimaalisen kiputason suhteen ruoansulatuskanavan leikkausten jälkeen Turun yliopistollisessa sairaalassa. Tulokset: Katsauksen tulokset viittaavat siihen, että potilaan psykologinen profiili vaikuttaa moniin leikkauksen jälkeiselle kivulle altistaviin tekijöihin. Näihin tekijöihin kuuluvat ahdistus, pelko, masennus, kivun odotus ja muut ruoansulatuskanavan leikkaukseen liittyvät tekijät. Tämän katsauksen tuloksissa kuvataan kuitenkin myös akuutti preoperatiivinen kipu, kirurgiset tekijät, genetiikka, ikä, sukupuoli, lihavuus ja aiemmat kokemukset kivusta merkityksellisinä altistavina tekijöinä ruoansulatuskanavan leikkauksen jälkeiselle kivulle. Ruoansulatuskanavan leikkauksen jälkeisiin kivunhoitostrategioihin kuuluu farmakologisten ja ei-farmakologisten toimenpiteiden käyttö. Kirjallisuuden mukaan ei-farmakologisia toimenpiteitä käytetään liian vähän, ja niitä olisi edistettävä farmakologisten kivunhoitostrategioiden lisänä elektiivisen ruoansulatuskanavan leikkauksen jälkeen. Kuvailevan ja vertailevan tutkimuksen tulokset ovat jossain määrin ristiriidassa nopean katsauksen tulosten kanssa. Aiemmat kipukokemukset tai aiempien kivuliaiden tapahtumien muistaminen eivät olleet yhteydessä ylimääräisen kipulääkityksen antamiseen leikkauksen jälkeen (p = 0,741). Leikkauksen jälkeiseen tulevaan kipuun liittyvä pelko ei ollut yhteydessä leikkauksen invasiivisuuteen (p = 0,662). Lisäksi kivun odotuksen (p = 0,698), tulevaan kirurgiseen toimenpiteeseen liittyvän kivun pelon (p = 0,637) ja leikkauksen jälkeisen lääkityksen (p = 0,481) välinen yhteys maksimaalisen leikkauksen jälkeisen kivun voimakkuuteen todettiin merkityksettömäksi. Tämän tutkimuksen tulokset viittaavat siihen, että potilaan odotukset ovat mahdollinen interventioalue, jolla voidaan parantaa leikkauksen jälkeistä kiputilannetta. Kipulääkityksen antaminen heräämössä ja kipulääkityksen määrä heräämössä olivat merkittäviä postoperatiivisen maksimaalisen kivun ennustajia (p = .001). Pohdinta: Katsauksen tulokset viittaavat siihen, että mukana olleissa tutkimuksissa on suuri tai kriittinen harhan riski. Postoperatiiviselle kivulle altistavat tekijät vaihtelivat suuresti eri tutkimuksissa, mutta niihin sisältyi pääasiassa psykologisia tekijöitä postoperatiivisen kivun tekijöinä. Kivunhoitostrategioihin olisi sisällyttävä yksilöllinen lähestymistapa, ja niitä olisi sovellettava ennen leikkausta, sen aikana ja sen jälkeen. Kuvailevassa ja vertailevassa tutkimuksessa on huomattavia vaikeuksia havaita kipuhistorian tai -kokemuksen vaikutusta leikkauksen jälkeiseen kipuun fysiologisen tai subjektiivisen raportoinnin avulla tietoisten yksilöiden osalta, koska on olemassa harhan riski ja koska käytetään yksiulotteista lähestymistapaa. Johtopäätökset: Kivunhoitostrategioihin olisi kuuluttava osallistujien biopsykososiaalisen profiilin huolellinen seulonta valintaleikkausta varten. Kuvaileva-vertaileva tutkimus viittaa siihen, että potilaiden tulevaan ruoansulatuskanavan leikkaukseen liittyvien kipuodotusten hallinnasta on mahdollista, joskin vähäistä hyötyä. Kipulääkkeiden määrä heräämössä on merkittävä leikkauksen jälkeisen maksimaalisen kivun ennustaja. Tulevaan tutkimukseen olisi sisällytettävä suurempi otos, enemmän kipuun liittyviä muuttujia ja jatkettava seurantaa.
Keywords: gastrointestinal, post-operative, pain, analgesia, anesthesia